Amphetamines analysis in wastewaters - method performance of solid phase extraction - higher performance liquid chromatography mass spectrometry techniques (SPE-HPLC MS/MS) - Ajao, Usman L.; Mustapha, Aliru Olajide (Technische Universität Dortmund, 2011)
Recently, many articles have reported different levels and distribution of amphetamine hitherto detected in biological fluids now appreciably found in aquatic environment at ng/L levels. Identification and measurement of amphetamine and its metabolites in surface and sewage waters using higher performance liquid chromatographic methodologies in the literatures now on current trend have provided information that are of scientific interest and effectively replaced immunological methods which only suggest the presence of these substances. Active research on both distribution and impacts of this important drug of abuse and related metabolites in the wastewaters are on-going.
EXCLI Journal ; Vol. 10, 2011
Keywords: amphetamine; drug metabolites; higher performance chromatography; solid phase extraction; wastewaters; 610